Measuring Empowering Leadership in Indonesia: A Rasch-based Validation Study. - Prihatsanti, Unika; Kusnadi, Annisa Puti (Pertanika Journal of Social Sciences & Humanities, 2026)
This study aimed to adapt and validate an Indonesian version of the Perceived Empowering Leadership (PEL-I) scale to measure employees' perceptions of empowering leadership. A total of 316 employees from various types of organisations in Indonesia participated in the study and completed the PEL-I scale using a five-point Likert format. Data were analysed using the Rasch measurement model with Winsteps software to examine the scale's psychometric properties. The results indicated high measurement quality, with person reliability of 0.94 and item reliability of 0.95. The analysis supported a unidimensional measurement structure, with 50.9% of the raw variance explained by the measures, and demonstrated good model fit, as indicated by an outfit mean square value of 1.05 and a significant chi-square statistic. Differential item functioning analysis identified potential item bias in one item across gender, educational level, and organisational type. These findings provide empirical support for the validity and reliability of the Indonesian PEL scale. The adapted instrument offers a valuable tool for assessing empowering leadership in organisational settings and can serve as a baseline measure for leadership development and future research in the Indonesian context.